Needs analysis for the development of ARVR-based teaching materials to support biodiversity literacy in Sebangau National Park - Fathul Zannah; Rahmatullah Rahmatullah; Muqor Rama Hasanah; Erni Yaya; Muhammad Noor Fitriyanto; Tety Zelisa (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Central Kalimantan is one of the regions in Indonesia that has high biodiversity, but unfortunately, this biodiversity is now threatened by various human activities and forest fires, which still frequently affect forests in Indonesia. In this study, we focus on analyzing teacher and student perceptions about the development of ARVR-based teaching materials, especially to support biodiversity literacy. The research method used was a qualitative descriptive design. Data collection was carried out by distributing questionnaires to two junior high school teachers and twenty junior high school students in Palangkaraya City, Central Kalimantan. The collected data were analyzed using descriptive analysis. The results of this research show that teachers have never developed their own teaching materials, especially ARVR-based materials that discuss rare plants and animals in Sebangau National Park, while students believe that the use of ARVR-based teaching materials will make learning activities more interesting. This research concludes that the development of ARVR-based teaching materials is a very important effort based on teacher and student perceptions, and it is important to continue in future research to develop the materials and test their effectiveness.Abstrak. Kalimantan Tengah merupakan salah satu daerah di Indonesia yang memiliki keanekaragaman hayati yang tinggi, namun sayangnya keanekaragaman hayati tersebut kini mulai terancam oleh berbagai aktivitas manusia dan kebakaran hutan yang masih sering melanda hutan-hutan di Indonesia. Dalam penelitian ini kami fokus untuk menganalisis persepsi guru dan siswa tentang pengembangan bahan ajar berbasis ARVR, khususnya untuk mendukung literasi keanekaragaman hayati. Metode penelitian yang digunakan adalah metode penelitian kualitatif deskriptif. Pengumpulan data dilakukan dengan menyebarkan kuesioner kepada 2 orang guru SMP dan kepada 20 siswa SMP di kota Palangkaraya Kalimantan Tengah. Data yang terkumpul dianalisis dengan menggunakan analisis deskriptif. Hasil penelitian menunjukkan bahwa guru belum pernah mengembangkan sendiri bahan ajar khususnya bahan ajar berbasis ARVR yang membahas tentang tumbuhan dan satwa langka di taman nasional sebangau, sedangkan siswa berpendapat bahwa penggunaan bahan ajar berbasis ARVR akan membuat kegiatan belajar menjadi lebih menarik. Penelitian ini menyimpulkan bahwa pengembangan bahan ajar berbasis ARVR sangat penting dilakukan berdasarkan persepsi guru dan siswa dan penting untuk dilanjutkan pada penelitian selanjutnya untuk mengembangkan bahan ajar tersebut dan menguji efektivitasnya pada penelitian selanjutnya.